2022
DOI: 10.1007/978-3-030-90355-8_26
|View full text |Cite
|
Sign up to set email alerts
|

Non-financial Disclosure and Materiality: Exploring the Role of CFOs

Abstract: This is the official book series of SIDREA -the Italian Society of Accounting and Business Administration. This book series is provided with a wide Scientific Committee composed of Academics by SIDREA. It publishes contributions (monographs, edited volumes and proceedings) as a result of the double blind review process by the SIDREA's thematic research groups, operating at the national and international levels. Particularly, the series aims to disseminate specialized findings on several topicsclassical and cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…They have found that preparers use materiality disclosures as image-enhancing marketing tools, which causes concerns regarding weak accountability and a deviation from the International Integrated Reporting Council's objective of improving the quality of information. Several studies have found an increase in the overall non-financial reporting quality (Cisi et al, 2022;, including only one study that used also relevance to proxy for reporting quality and documented that the legal obligation of non-financial disclosure (NFD) had a positive effect on the relevance of reports. However, this study compared voluntary reports with mandatory reports prepared in selected EU countries based on various national regulations in the field of non-financial reporting prior to the introduction of the Directive.…”
Section: Introduction and Research Questionsmentioning
confidence: 99%
“…They have found that preparers use materiality disclosures as image-enhancing marketing tools, which causes concerns regarding weak accountability and a deviation from the International Integrated Reporting Council's objective of improving the quality of information. Several studies have found an increase in the overall non-financial reporting quality (Cisi et al, 2022;, including only one study that used also relevance to proxy for reporting quality and documented that the legal obligation of non-financial disclosure (NFD) had a positive effect on the relevance of reports. However, this study compared voluntary reports with mandatory reports prepared in selected EU countries based on various national regulations in the field of non-financial reporting prior to the introduction of the Directive.…”
Section: Introduction and Research Questionsmentioning
confidence: 99%